Pengaruh sosio demografi dan kemampuan terhadap minat berwirausaha mahasiswa/i fakultas ekonomi di universitas islam riau - Tya Sakdiah Putri; Lestari Ganarsih; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at the Faculty of Economics at the Islamic University in Jalan Riau Kaharudin Nasution No. 28 284 113 Marpoyan stop Pekanbaru, this study aimed to determine the effect of Socio Demographic and Student Entrepreneurship Capabilities variables Faculty of Economics at the Islamic University of Riau. The population in this study is the eighth semester students (VIII) of the Faculty of Economics in Riau Islamic University majoring in Accounting, Management, and Economics totaled 474 students, the technique used was cluster sampling is obtained with a sample of 83 students. Methods of data collection using questionnaire and analysis method used is multiple linear regression method using the SPSS program. From the results of testing that has been done, simultaneous regression test (F test) showed that the independent variables studied, namely Socio-Demographic and Entrepreneurship Capabilities positive and significant impact on the dependent variable is student interest in entrepreneurship. The amount of influence that arise (R2) by these two variables by 53.7%, while the remaining 46.3% is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied were the Socio Demographics have a positive and significant effect on the dependent variable is the interest in entrepreneurship, entrepreneurial ability while the variable has a positive and significant influence also on the variable Interest in entrepreneurship is bound students.Keywords: Interest in Entrepreneurship, Socio-Demographics and Ability